If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1h = 11 Solving 5 + -1h = 11 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1h = 11 + -5 Combine like terms: 5 + -5 = 0 0 + -1h = 11 + -5 -1h = 11 + -5 Combine like terms: 11 + -5 = 6 -1h = 6 Divide each side by '-1'. h = -6 Simplifying h = -6
| -21+8x=4x+31 | | a+2b+3c+3a+3b= | | 2(x+1)-3(1-x)=2 | | 2x+10-4=36 | | k=2/3 | | 4g+11=31 | | -14-3x=25-6x | | -49+8y=19 | | u-4u=7 | | -3w+4(3w-1)=16-w | | -19-6x=8x+13 | | 29-16= | | -26-8x=8x+12 | | T+T+27=65 | | -0.75(4r+8)=12 | | -7(3x-6)=-21x+42 | | (7w+6)(5w-13)= | | 30x-24xy= | | 1.33(19)= | | a+b+3b= | | 1.33(18)= | | 1.33(17)= | | 1.33(16)= | | 3r+9(r-2)= | | f(x)=x^2-12 | | 1.33(14)= | | (3.141511263)(1234567890)= | | 2(z-7)=3z | | 1.33(13)= | | (-0.75)x+4=(-2) | | 1.33(12)= | | 5(n+7)+7=-9 |